2014
DOI: 10.1038/ncomms4092
|View full text |Cite
|
Sign up to set email alerts
|

Switching plastic crystals of colloidal rods with electric fields

Abstract: When a crystal melts into a liquid both long-ranged positional and orientational order are lost, and long-time translational and rotational self-diffusion appear. Sometimes, these properties do not change at once, but in stages, allowing states of matter such as liquid crystals or plastic crystals with unique combinations of properties. Plastic crystals/glasses are characterized by long-ranged positional order/frozen-in-disorder but short-ranged orientational order, which is dynamic. Here we show by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
122
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 35 publications
3
122
1
Order By: Relevance
“…This sequence of events implies that, as far as we can determine, a continuous transition from a plastic crystal to a crystal took place. As far as we know, such a transition in the rotational behavior has not been observed in bulk phases, except when an external electric field was used [22]. Lee et al reported a similar monolayered crystal but composed of dumbbell particles with a nearly hard potential oriented perpendicular to the wall [18].…”
Section: Prl 115 078301 (2015) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 93%
See 2 more Smart Citations
“…This sequence of events implies that, as far as we can determine, a continuous transition from a plastic crystal to a crystal took place. As far as we know, such a transition in the rotational behavior has not been observed in bulk phases, except when an external electric field was used [22]. Lee et al reported a similar monolayered crystal but composed of dumbbell particles with a nearly hard potential oriented perpendicular to the wall [18].…”
Section: Prl 115 078301 (2015) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 93%
“…Recent advances in quantitative threedimensional (3D) real space analysis have made it possible to measure both positions and orientations of rodlike particles with high accuracy and sufficient temporal resolution [20][21][22][23]. In a 3D bulk phase at the same packing fraction of ϕ ¼ 0.0026 the rods were found to form a body centered cubic (bcc) plastic crystal and to rotate freely in all directions [22]. Confined between two parallel plates, however, their rotational freedom in the z direction (perpendicular to the walls) was now found to be completely or partially restricted as a function of the wall separation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A dispersion of silica microrods has been shown to generate unique crystal phase behaviour when exposed to external electric fields. 11 One of the advantages of silica is the ease at which chemical modification of the particle surface can be achieved due to the reactivity of the terminal Si-OH bonds. A vast range of different functionalities can be attained through post-modification including, but certainly not limited to, fluorescent moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the strength and range of the interaction, colloidal suspensions show a variety of different phases as fluid, solid crystals with crystal lattice structures as body-centered cubic (bcc) or face-centered cubic (fcc), and even glassy morphology. [9][10][11] Besides the common spherical particles, systems composed of particles with other geometries like rods, 12,13 ellipsoids, 14,15 or cubes 16,17 were also studied recently, and some new fascinating phase behaviors have been found.…”
Section: Introductionmentioning
confidence: 99%